Providers' lack of knowledge about herpes zoster in HIV-infected patients is among barriers to herpes zoster vaccination. (June 2013) - Aziz, M; Kessler, H; Huhn, G
Summary: Identification of perceptions about herpes zoster (HZ) disease, vaccine effectiveness and safety, and vaccine recommendations may impact immunization practices of physicians for HIV-infected patients. A survey was used to quantify knowledge of HZ as well as determine physician immunization perceptions and practices. There were 272/1700 respondents (16%). Correct answers for the incidence of varicella zoster virus (VZV) infection in adults and incidence of HZ in HIV-infected patients were recorded by 14% and 10% of providers, respectively. Providers reported poor knowledge of the incidence of disease recurrence in HIV-infected patients (41% correct), potency of HZ vaccine (47.5% correct) and mechanism of protection against reactivation of VZV (66% correct). Most (88%) agreed that HZ was a serious disease, and 73% believed that the burden of disease made vaccination important. A majority (75%) did not vaccinate HIV patients with HZ vaccine regardless of antiretroviral therapy status. Barriers to administration included safety concerns, concern that vaccine would not prevent HZ, risk of HZ dissemination, reimbursement issues and lack of Infectious Diseases Society of America (IDSA) guidelines. Only 38% of providers agreed that CDC guidelines were clear and 50% believed that clinical trials were needed prior to use of HZ vaccine in HIV-infected patients. Education about HZ is needed among HIV providers. Providers perceived vaccination as important, but data on vaccine safety and clear guidance from the CDC on this issue are lacking.